2019
DOI: 10.1080/01443410.2018.1537479
|View full text |Cite
|
Sign up to set email alerts
|

The role of personality in motivational regulation and academic procrastination

Abstract: This study explores the role of the motivational self-regulation in academic procrastination under the personality framework. Therefore, the aims of the study were to investigate: (a) the role of personality dimensions in the self-regulation of motivation; (b) the role of self-regulation of motivation in procrastination; and (c) the mediating role of the self-regulation of motivation. The participants were 274 university students (M ¼ 21 years). The Big Five traits explained from 6% to 17% variance of the indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 50 publications
1
18
0
7
Order By: Relevance
“…Both hypotheses were fulfilled. In the first case, the results confirm prior evidence, since personality components were associated with relatively stable coping strategies [64][65][66]. The more harmful emotion-focused strategies were predicted by the N factor, characterized by low self-regulation, while the C factor was usually associated with problem-focused strategies, typical of high self-regulation, and strategies associated with factors E, O, and A were mixed, typical of medium SR [67][68][69].…”
Section: Discussionsupporting
confidence: 82%
“…Both hypotheses were fulfilled. In the first case, the results confirm prior evidence, since personality components were associated with relatively stable coping strategies [64][65][66]. The more harmful emotion-focused strategies were predicted by the N factor, characterized by low self-regulation, while the C factor was usually associated with problem-focused strategies, typical of high self-regulation, and strategies associated with factors E, O, and A were mixed, typical of medium SR [67][68][69].…”
Section: Discussionsupporting
confidence: 82%
“…worries a lot, poor impulse control, emotional instability), and intellect/openness (e.g. curious about many different things) [15,16]. Personality is a very important and vital part of a person's life is also very complex where an individual reacts and interacts with other individuals [17].…”
Section: Issn: 2089-9823 mentioning
confidence: 99%
“…Besides mastery-approach, it seems that self-regulation of motivation may also be important factor for experiencing flow. There are several self-regulating motivational strategies that students use to enhance motivation (Walters, 1998;Ljubin-Golub, Petričević, & Rovan, 2019). Previous research found that mastery self-talk strategy was the most important predictor of academic flow (Ljubin-Golub, 2019).…”
Section: Introductionmentioning
confidence: 99%